GroEL and Lipopolysaccharide from Francisella tularensis Live Vaccine Strain Synergistically Activate Human Macrophages - Noah, Courtney E. (American Society for Microbiology (ASM), 2010)
Francisella tularensis, the causative agent of tularemia, interacts with host cells of innate immunity in an atypical manner. For most Gram-negative bacteria, the release of lipopolysaccharide (LPS) from their outer membranes stimulates an inflammatory response. When LPS from the attenuated live vaccine strain (LVS) or the highly virulent Schu S4 strain of F. tularensis was incubated with human umbilical vein endothelial cells, neither species of LPS induced expression of the adhesion molecule E-selectin or secretion of the chemokine CCL2. Moreover, a high concentration (10 μg/ml) of LVS or Schu S4 LPS was required to stimulate production of CCL2 by human monocyte-derived macrophages (huMDM). A screen for alternative proinflammatory factors of F. tularensis LVS identified the heat shock protein GroEL as a potential candidate. Recombinant LVS GroEL at a concentration of 10 μg/ml elicited secretion of CXCL8 and CCL2 by huMDM through a TLR4-dependent mechanism. When 1 μg of LVS GroEL/ml was added to an equivalent amount of LVS LPS, the two components synergistically activated the huMDM to produce CXCL8. Schu S4 GroEL was less stimulatory than LVS GroEL and showed a lesser degree of synergy when combined with Schu S4 LPS. These findings suggest that the intrinsically low proinflammatory activity of F. tularensis LPS may be increased in the infected human host through interactions with other components of the bacterium.